Conduction System Pacing for Post Transcatheter Aortic Valve Replacement Patients: Comparison With Right Ventricular Pacing - Hong-Xia Niu (Frontiers Media S.A., 2021)
Introduction: For patients who develop atrioventricular block (AVB) following transcatheter aortic valve replacement (TAVR), right ventricular pacing (RVP) may be associated with adverse outcomes. We assessed the feasibility of conduction system pacing (CSP) in patients who developed AVB following TAVR and compared the procedural and clinical outcomes with RVP.Methods: Consecutive patients who developed AVB following TAVR were prospectively enrolled, and were implanted with RVP or CSP. Procedural and clinical outcomes were compared among different pacing modalities.Results: A total of 60 patients were enrolled, including 10 who were implanted with His bundle pacing (HBP), 20 with left bundle branch pacing (LBBP), and 30 with RVP. The HBP group had significantly lower implant success rate, higher capture threshold, and lower R-wave amplitude than the LBBP and RVP groups (p < 0.01, respectively). The RVP group had a significantly longer paced QRS duration (153.5 ± 6.8 ms, p < 0.01) than the other two groups (HBP: 121.8 ± 8.6 ms; LBBP: 120.2 ± 10.6 ms). During a mean follow-up of 15.0 ± 9.1 months, the LBBP group had significantly higher left ventricular ejection fraction (LVEF) (54.9 ± 6.7% vs. 48.9 ± 9.1%, p < 0.05) and shorter left ventricular end-diastolic diameter (LVEDD) (49.7 ± 5.6 mm vs. 55.0 ± 7.7 mm, p < 0.05) than the RVP group. While the HBP group showed trends of higher LVEF (p = 0.016) and shorter LVEDD (p = 0.017) than the RVP group. Four patients in the RVP group died—three deaths were due to progressive heart failure and one was due to non-cardiac reasons. One death in the LBBP group was due to the non-cardiac reasons.Conclusions: CSP achieved shorter paced QRS duration and better cardiac structure and function in post-TAVR patients than RVP. LBBP had a higher implant success rate and better pacing parameters than HBP.